Epidemiological trend and age-period-cohort effects on cardiovascular disease mortality and disability-adjusted life years attributable to dietary risks and high body mass index at the regional and country level across China and Pakistan - Yan, Wu; Yan, Xiuzhen; Mubarik, Sumaira; Nawsherwan, (Frontiers in Nutrition, 2023)
Background: Modifiable risk factors are major drivers of cardiovascular disease (CVD). We aimed to determine the epidemiological trend and age-period-cohort effects on CVD burden attributable to dietary risks and high body mass index (BMI) across China and Pakistan from 1990 to 2019. Methods: Data on the all-ages and age-specific CVD burden, age-standardized CVD mortality and disability-adjusted life years (DALYs) rates were obtained from the Global Burden of Disease Study 2019. Joinpoint regression analysis was conducted to find temporal trends and age-period-cohort (APC) modeling was used to estimate age, period, and cohort effects on CVD burden. Results: Between 1990 and 2019, the all-ages CVD burden attributable to dietary risks and high BMI increased by 2-3-fold in China and by 3-5-fold in Pakistan. The diet-related CVD age-standardized mortality rate (ASMR) and age-standardized disability-adjusted life years (DALYs) rate significantly decreased in China but increased in Pakistan. Both countries showed a marked increasing trend of CVD ASMR and the age-standardized DALYs rate attributable to high BMI. Taiwan in China showed a remarkable reduction in CVD burden. However, in Pakistan, all regions observed a significantly increasing trend of CVD burden attributable to modifiable risk factors. A higher risk ratio of premature CVD mortality (<70 years) was observed among Chinese attributable to high BMI and among Pakistani attributable to dietary risks. In China, early birth cohorts showed a higher risk ratio and recent birth cohorts experienced a lower risk ratio of CVD burden compared with Pakistan. Conclusion: In conclusion, dietary risks and high BMI caused a huge CVD burden across China and Pakistan.